Zeolite-Loaded Titanium Dioxide Photocatalytic Cement-Based Materials for Efficient Degradation of Drinking Water Disinfection Byproduct Trichloroacetamide - Liao, Gang; She, Anming; Chu, Wenhai; Zuo, Junqing; Yao, Wu (Frontiers in Materials, 2021)
A two-step method was used to load TiO2 on cement matrix, and zeolite was chosen as intermediate support. TiO2@Zeolite composite coated photocatalytic cement-based material (PCM) was prepared. Some advanced characterization technologies including X-Ray Diffraction (XRD), scanning electronic microscopy (SEM), energy dispersive X-ray spectroscopy (EDS), and BET specific surface area test were applied to characterize the physicochemical properties of as-prepared PCM. And photocatalytic degradation of trichloroacetamide (TCAcAm) was conducted to evaluate its photocatalytic efficiency. Results show that TiO2@Zeolite composite can improve the adsorption ability of PCM and TiO2 particles was dispersed on the surface of a PCM homogeneously and provide abundant active sites for photocatalytic reactions. Moreover, TiO2@Zeolite composite can reduce the negative effect of cement on TiO2. The synergetic effect of TiO2@Zeolite composite can remarkably improve the photocatalytic degradation rate, reaching up to 97.8%. TiO2@Zeolite composite coated photocatalytic cement-based material holds great promise to eliminate water pollution.